Where are all the egg genes? - Maniates, Katherine A.; Singson, Andrew (Frontiers in Cell and Developmental Biology, 2023)
Complementary forward and reverse genetic approaches in several model systems have resulted in a recent burst of fertilization gene discovery. The number of genetically validated gamete surface molecules have more than doubled in the last few years. All the genetically validated sperm fertilization genes encode transmembrane or secreted molecules. Curiously, the discovery of genes that encode oocyte molecules have fallen behind that of sperm genes. This review discusses potential experimental biases and inherent biological reasons that could slow egg fertilization gene discovery. Finally, we shed light on current strategies to identify genes that may result in further identification of egg fertilization genes.